1969
DOI: 10.1007/bf02531003
|View full text |Cite
|
Sign up to set email alerts
|

Flotation rates, molecular weights and hydrated densities of the low‐density lipoproteins

Abstract: A method involving three computer programs is described for characterizing the major component of the Sf 0–12 low‐density lipoprotein class by its Sf rate, hydrated density and molecular weight. All necessary information is obtained from a standard low and high‐density lipoprotein ultracentrifugal analysis. Moving‐boundary flotation rates are measured in 1.061 g/ml sodium chloride and 1.200 g/ml sodium bromide solutions and are corrected to flotation at zero concentration. Hydrated densities are calculated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 14 publications
1
43
0
1
Order By: Relevance
“…When based on the same assumption and measured parameters, the molecular weights (2.38 x 106-2.58 x 106) of LD lipoprotein subfractions (LDL-IV, LDL-V and LDL-VI) of comparable hydrated densities were within the range reported in the literature. However, the inverse relationship between the hydrated density and molecular weight (Lindgren et al, 1969) within these three density ranges was not observed. Frictional ratios of LDL-V and LDL-VI subfractions clearly indicate that these lipoproteins were hydrated and/or deviated from a spherical shape.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…When based on the same assumption and measured parameters, the molecular weights (2.38 x 106-2.58 x 106) of LD lipoprotein subfractions (LDL-IV, LDL-V and LDL-VI) of comparable hydrated densities were within the range reported in the literature. However, the inverse relationship between the hydrated density and molecular weight (Lindgren et al, 1969) within these three density ranges was not observed. Frictional ratios of LDL-V and LDL-VI subfractions clearly indicate that these lipoproteins were hydrated and/or deviated from a spherical shape.…”
Section: Discussionmentioning
confidence: 79%
“…Lindgren et al (1969) found a molecular weight of 2.12 x 106 for LD lipoprotein from men and 2.36 x 106 for women, whereas Adams & Schumaker (1969) found values of 2.1 x 106-2.6 x 106. When based on the same assumption and measured parameters, the molecular weights (2.38 x 106-2.58 x 106) of LD lipoprotein subfractions (LDL-IV, LDL-V and LDL-VI) of comparable hydrated densities were within the range reported in the literature.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Results are also described for the peak flotation rate (S f ) of the LDL-mass distribution [12,13]. Plasma lipoprotein cholesterol concentrations were measured directly by the methods of the Lipid Research Clinics [14], plasma apolipoprotein B concentrations were assessed by radioimmunoassay [15], apolipoprotein A-I and A-II concentrations were measured by radialimmunodiffusion [16], and LCAT mass was measured by double antibody radioimmunoassay [17].…”
Section: Subjects and Laboratory Measurementsmentioning
confidence: 99%